PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP HASIL BELAJAR MATERI TATANAMA SMAN 1 KUANTAN MUDIK - Ahmad Faizan (Universitas Islam Kuantan Singingi, 2020)
This study aims to determine the effect of 5E Learning Cycle against studen learning in nomenclature material and chemical reaction equations. This research was conducted in kuantan mudik SMAN 1 academic year 2018-2019. The method used in this study is quasi experimental methods, whit research design namely desain Pretes-Posttest Control Group Design. The sample of this study was the student of class X MIPA 1 as the experimental class who were treated whit 5E Leraning Cycle models and student ofclass X MIPA 3 taken based on the untreated control class taken based on the technique Cluster Random Sampling. The instrument used in this research is 25 written questios in the form of multipe choice instruments which have been tested of content validity, item analysis, and reliability. The content validity test was carried out by 3 judgementvalidators while the analyzed using the help of multiple choice ANATES. The hipotesis test used is an independent t-test on the right side with the help of SPSS vesion 20 and the value sig = 0,000 > 0,05. The result of this study indicate that the average N-Gain oflearning outcomes of students using 5E learning cycle is higher than the average N-Gain student learning outcomes uising conventional material on nomenclature and chemical reaction equations class X MIPA SMAN 1 Kuantan Mudik.